DOES THE CURRENT REGIONAL AUTONOMY SUPPORT LEGAL PLURALISM IN INDONESIA? - Andy Omara (Fakultas Hukum Universitas Gadjah Mada, 2011)
This article attempts to analyse Indonesia’s legal system. We will discuss how the dynamics of constitutional arrangement affect regional authorities. The correlation between regional autonomy and legal pluralism, for instance the unique implementation of sharia law in Aceh province, will also be discussed. Tulisan ini membahas sistem hukum Indonesia. Dalam tulisan ini akan dianalisis bagaimana dinamika aturan konstitusi mempengaruhi kewenangan daerah. Hubungan antara otonomi daerah dengan pluralisme sistem hukum, misalnya penerapan hukum syariah di provinsi Aceh, juga akan dibahas di sini.